Removing Barriers of Access to Services - A Case of National Water and Sewerage Corporation (Uganda) - Okaronon, Edmond; Amayo, Johnson (Core, 2005)
Water is both an economic and a social good. A balance needs to be established between access and cost of service delivery. It is an established fact that the poor pay for water at a much higher rate than that levied by the utility at the Public Stand Pipes (PSPs) due to the middle man effect. NWSC developed a strategy to reduce reliance on PSPs and encourage individual connections by which the poor get water at the actual utility price. Under the policy, materials and labour costs for implementation of the new connection is met by the corporation. The Corporation also took over responsibility of repair of service pipes. The main objectives of the policy were to increase access and curb high level of UFW. As a result, the rate of new connections has increased from 14,000 in the FY2003/04 to about 20,240 in the FY2004/05. Similarly, Unaccounted for Water reduced from 37.6% to 33.9% respectively. Generally, the main objectives for implementing the policy have been achieved despite a number of challenges encountered.brought to you by COREView metadata, citation and similar papers at core.ac.ukprovided by Loughborough University Institutional Repository